Thibang Diphatlha: a sequential multiple assignment randomized trial designed to increase timely adoption of cervical cancer treatment in Botswana - Katharine A. Rendle; Doreen Ramogola-Masire; Surbhi Grover; Thibang Diphatlha Collective (Implementation Science Communications)
Abstract Background Delays and missed opportunities for timely treatment contribute significantly to stark inequities in cervical cancer mortality in low- and middle-income countries (LMICs) compared to high-income countries. The vast majority (approximately 90%) of new cases and deaths occur in LMICs, particularly those with high rates of HIV such as Botswana. To date, most of the implementation and cancer control research in Botswana and other LMICs has focused on cancer prevention and screening, with limited focus on cancer treatment. As such, there is a critical need to identify effective strategies to ensure timely care, and to understand contextual factors that shape the response to strategies. Without this fundamental knowledge, cervical cancer will remain a public health crisis in Botswana and other LMICs. Methods To help fill this known gap, this study tests the effectiveness of adaptive strategies on timely treatment adoption using a hybrid (type III) Sequential Multiple Assignment Randomized Trial (SMART) design and evaluate contextual mechanisms contributing to the success or failure of each adaptive strategy. The adaptive strategies are designed to target contextual determinants identified in our prior work, including delayed communication of results to patients, individual and structural barriers to accessing treatment, and suboptimal care coordination between referring and cancer treatment clinics, and are supported by systematic evidence of the effectiveness of nudge strategies in clinical care. The primary implementation outcome is adoption, defined as the initiation of treatment within 90 days. Secondary outcomes include fidelity, reach, acceptability, implementation costs, and cancer and HIV-related clinical outcomes. The rationale for the study is that enhancing coordination, communication, and navigation through centralized outreach will both increase timely treatment adoption and be scalable and sustainable after the project is completed. Discussion This innovative study seeks to decrease cervical cancer mortality in LMICs by developing and implementing effective and sustainable strategies that can be sustained and adapted to other contexts. Additionally, this study seeks to advance the long-term impact of global implementation science through strong and sustained partnerships in Botswana and other LMICs. Trial registration ClinicalTrials.gov NCT05952141. Registered on July 11, 2023. https://clinicaltrials.gov/study/NCT05952141 Protocol version and date Version 1 (September 28, 2024).